India's political economy - "Lewis, John P." (Delhi, 1997)
In India's Political Economy an American analyst of Indian economic development looks at the way the interplay between markets and governments (and of his own thinking about the subject) has evolved over the past thirty-five years.
Keywords: India political situations and condition